Crown Lengthening Surgery for Enhancing Restorative Treatment in Esthetic Zone - Dawadi, A.; Humagain, M.; Sapkota, B.; Subba, M.; Neupane, M.; Lamichhane, S. (Kathmandu University Medical Journal, 2021)
For obtaining adequate retention for restoring cases like subgingival caries or extensive caries that shortens the tooth, short clinical crown, and fractures, it is usually necessary to disclose more tooth structure. Crown lengthening procedure is done to increase the clinical crown length for restorative or esthetic reasons without breaching the biologic width. These procedures are also utilized to improve the appearance and retention of restorations placed within the esthetic zone. We report a case of crown lengthening surgery with an internal bevel gingivectomy which was done in our department without compromising tooth support and esthetics.